The Relationship of the Influence of Social Media on Personal Hygiene in Adolescents at Amal Luhur Private Junior High School in Medan - Beatric Febrica Rumahorbo (Journal of Social Research, 2025)
This study aims to determine the relationship between the influence of social media use and personal hygiene among adolescents at Amal Luhur Private Junior High School in Medan. The background of this study is based on the increasing use of social media among teenagers, which can affect their health behaviors, including personal hygiene. This research employed a survey design with a cross-sectional approach. The population consisted of all eighth-grade students at Amal Luhur Private Junior High School, with a total sample of 38 respondents selected through total sampling. The research instrument was a questionnaire assessing the level of social media use and personal hygiene behavior. Data were analyzed using the chi-square test. The results showed that most respondents had poor personal hygiene (57.9%) and high social media use (52.6%). The statistical test yielded a p-value of 0.043 (p < 0.05), indicating a significant relationship between social media use and personal hygiene among adolescents. These findings suggest that higher intensity of uncontrolled and non-educational social media use correlates with lower levels of personal hygiene. Therefore, active involvement from parents and schools is essential in guiding teenagers to use social media positively and educationally to promote clean and healthy living behaviors.